Evaluation of the TRANSIA® PLATE Staphylococcal Enterotoxins Kit for the Detection of Staphylococcal Enterotoxins in Selected Foods. (23rd November 2019) - Kerr, David E; Bergfalk, Cory; Feldsine, Philip T; John, Lisa; Tallent, Sandra; Hammack, Thomas; Brodsky, Michael
Abstract: The TRANSIA ® PLATE Staphylococcal Enterotoxins enzyme immunoassay (EIA) was validated according to AOAC INTERNATIONAL guidelines forvalidating qualitative binary chemistry and microbiological methods. Five food matrixes were analyzed to determine the probability of detection (POD) forstaphylococcal enterotoxins (SE), including SEA, SEB, SEC1, SEC2, SEC3, SED, and SEE, by the TRANSIA PLATE Staphylococcal Enterotoxins EIA. The food matrixes tested were food types implicated in staphylococcal enterotoxin outbreaks and included raw milk cheese, liquid infant formula, eclairs, ready-to-eat ham, and canned mushrooms. Cheese and infant formula weretested with and without dialysis/concentration. Theinfant formula was also tested by an independent laboratory. Each food matrix was inoculated with specific toxins at low levels to yield fractional recoveries (0.015–0.20 ng/g of food) for POD analysis. One hundred percent recovery was achieved at concentrations ranging from <0.10 ng/g to 0.25 ng/g of toxin in the various food matrixes. At the same time, 50 Staphylococcus aureus strains known to produce toxins and 30 non–toxin producing bacteria (including 22 Staphylococcus strains) were grown and tested. All the SE toxin–producing strains yielded positive results and all of the exclusivity strains were negative. Robustness studies showed that changes in sample volume, sample pH, and EIA assay temperature had no significant effect on performance. Stability studies showed that kits stored for 12+ months performed as well as newly made kits. This assay has been approved as a Performance TestedMethod SM .